Prevalence of Pulmonary and Extrapulmonary Tuberculosis Among the Patients Attending Community Based Medical College, Bangladesh (CBMC,B) Hospital (Community Based Medical Journal, 2025)
Tuberculosis (TB) is a chronic granulomatus bacterial infection affecting almost all organs of the body and classified as pulmonary TB (PTB) and extrapulmonary TB (EPTB). In our country, tuberculosis is still a havoc in community health. This retrospective study by reviewing case records was conducted in Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, to estimate the prevalence of pulmonary and extrapulmonary tuberculosis among the patients attending the hospital between January 2022 and June 2024. Data  were collected from the patients’ records – a total of 67 patients admitted under Surgery, ETN and Medicine units of the hospital. 20(29.85%) of the patients were diagnosed with PTB, while 47(70.15%) had EPTB. Out of 67 patients, 29(43.28%) were male and 38(56.72%) were female; male-female ratio was 1:1.31. Based on occupations, housewives were the highest in numbers (45%), followed by students (18%), farmers (13%), service holders (12%), day labourers (10%) and drivers (2%). Pulmonary TB was more prevalent among the 51-60 years age group (25%), followed by the 71-80 age group (20%). Extrapulmonary TB was more prevalent among the 21-30 years age group (29.8%), followed by the 31-40 years age group (23.4%). A male predominance (65%) was observed compared to female (35%) in PTB; in contrast, a female predominance (66%) was observed compared to male (34%) in EPTB. Among EPTB patients, cervical lymph nodes TB was found in 22(46.8%), followed by breast TB 8(17%), axillary TB 7(14.9%) and abdominal TB 3(6.4%). Tubercular abscess was diagnosed in 7(14.9%) cases. More and more TB awareness campaigns in the community educating people on mode of transmission of TB and self-assessment along with early diagnosis and prompt treatment can improve the situation to a great extent.  CBMJ 2025 January: Vol. 14 No. 01 P: 81-84